Micronutrient Mineral and Nutrient Content of Volcanic Soils and Creeks from the Montserrat Soufriere Hills Volcano. Nature’s Fertilizer: Mineral Nutrient Content of Volcanic Soils - Tulp, Orien L; Sainvil, Frantz; Branly, Rolando; Sciranka, Andrew; Guibert, Roberto; Einstein, George P (European Journal of Applied Sciences, 2023)
Agricultural soils and potable water supplies provide a major source of minerals known to be essential for plant and animal health. After several hundred years of relative quiescence, the Soufriere Hills Volcano of Montserrat roared back to life in 1995 through 1997, wreaking severe havoc and severe damage to the geography and ecosystems and serious immediate and chronic health risks to the remaining inhabitants of the Island. The pyroclastic ash flow reached temperatures of 1500 °F and progressed down the hillsides at speeds of 80 mph, causing incineration and virtual destruction of everything in its path, while the gaseous and particulate laden plume reached altitudes of 7 miles (10.7 km), impacting air quality and aircraft navigation in the region. A total of 19 individuals became entrapped in the lava flow, and perished quickly as a direct result of the volcanic eruption. Volcanic soils derive from deeper layers of the earths surfaces and are notoriously rich in mineral nutrients representative of those deep mineral deposits. While virtually all combustible objects in the path of the raging ash flow become incinerated within minutes, the aftermath of the eruptions delivers the mineral rich constituents over a wide swath of the surrounding geography often reaching miles from the volcanic origin. Soils and consumable water sources are well known to provide a reliable community source of essential minerals in human nutrition, and in their chronic absence, numerous pathologic sequela may develop. To determine the mineral content of surrounding surface soils, samples of surface ash layers and nearby creeks were obtained from 7 regions and 3 free-flowing creeks and subjected mineral analysis. The surface ash specimens contained abundant amounts of the nutrients Iron, Calcium, Sodium, Magnesium, Sulfur, and non-nutrient Aluminum, intermediate amounts of potassium, Phosphorous, and Manganese, and small amounts of Boron, Copper and Zinc. Creek water runoff originating from higher elevations was consistently acidic with a healthy mean pH of 5.1, and contained smaller proportions of the same minerals, reflective of their relative effective solubility in the acidic water. Thus, the volcanic ash flow while devastating to the environment and public health in the immediate aftermath, provided numerous minerals important to plant and animal nutrition and to human health and health water sources which contributed to the longer-term reinstitution of edible plants and to the recovery of the vibrant lush greenery of the Emerald Isle of the Caribbean.